SCIENCE OF COSMOS VERSES, ORIGIN OF THE UNIVERSE AND ITS EXTENSION (Study of the Macrocosm from the perspective of the Al-Qur’an) - Prakoso, Theo Jaka (Universitas Islam Negeri Alauddin Makassar, 2019)
The study of the characteristics of various kinds of energy in the universe has become the main source of human success, to achieve his faith in God. One of them with a scientific proof of the truth of the Al-Qur’an against science that has been tested theoretically and empirically must also be in accordance with what is stated in the Al-Qur’an. This study aims to find a meeting point of the Al-Qur’an with modern science about the interpretation of the verses of the cosmos regarding the origin and extinction of the universe. The information provided by the Al-Qur’an will remain confidential, until the human mind is able to properly digest the information. As time goes by and the development of science, Allah gradually proves the truth of the Al-Qur’an' information about the universe. The results of this study indicate that the Al-Qur’an has far preached the theory of the universe before modern science revealed it in a study.